MODEL PERSAMAAN REGRESI PERILAKU PARKIR PENGENDARA WANITA DAN PRIA DI PALEMBANG INDAH MALL (PIM) - Ramadhani Ramadhani (TEKNIKA: Jurnal Teknik, 2015)
The research objective of Regression Equation Model Behavior Women Riders parking in Palembang Indah Mall ( PIM ) to obtain regression model was chosen in the group of men and women , so that it can be stated that the variables that have a dominant influence on the parking time is the frequency of visits. While the ability to drive influence covered by the influence of frequency. That is however the condition of driving ability as long as it has the frequency of visits are frequent, parking time will be brief. The regression model obtained consisting of : Regression Equation Model for Women in PIM parking time : Wpw = 57.325-0.451 F and Model Regression Equations for Men parking time in PIM : Wpp = 43.485-0.442 F. Keywords : Regression Equation Model, parking time.